Abdominal aortic spectral Doppler combined with echocardiography can improve the diagnostic sensitivity of aortic coarctation in pediatric patients - Liu, Qianjun; Hu, Yuan; Peng, Yinghui; Li, Wenfeng; Chen, Wenjuan; Luo, Jinwen; Liu, Jinqiao; Deng, Xicheng (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to investigate the clinical value of abdominal aortic spectral Doppler combined with echocardiography in the diagnosis of aortic coarctation in pediatric patients.MethodsPediatric patients with aortic coarctation, diagnosed by computed tomography angiography (CTA) and surgically confirmed, were retrospectively enrolled. These patients were divided into two groups based on the availability of abdominal aortic spectral Doppler. Additionally, both abdominal aortic spectral Doppler and echocardiographic data were collected for the normal group. All data were compared and analyzed to determine the reasons for discrepancies in diagnostic results.ResultsNo significant differences were observed in baseline characteristics among the three groups (p > 0.05). There were statistically significant differences in aortic isthmus velocity and aortic isthmus Z-scores between the normal group and the two patient groups (p < 0.05), but there were no significant differences in aortic isthmus velocity or aortic isthmus Z-scores between the two patient groups (p > 0.05). The abdominal aortic spectral Doppler group demonstrated significantly decreased peak systolic velocity (PSV), prolonged acceleration time (AT), and reduced pulsatility index (PI) and resistance index (RI) compared with controls (p < 0.05). Echocardiographic detection rates differed between groups: non-abdominal aortic spectral Doppler group, 59 true-positive coarctation cases (sensitivity 85.5%, false-negative rate 14.5%); abdominal aortic spectral Doppler group, 75 true-positive cases (sensitivity 96.2%, false-negative rate 3.8%). The combined diagnostic model incorporating abdominal aortic PSV, AT, and aortic isthmus Z-score achieved superior performance (AUC = 0.98), significantly outperforming individual parameters.ConclusionsAbdominal aortic spectral Doppler combined with echocardiography can improve the diagnostic sensitivity of aortic coarctation in pediatric patients and can be used as an important indirect imaging approach in clinical practice to reduce missed diagnoses of aortic coarctation.